(untitled) - Brown, H. Douglas (New Jersey, US, 1992)
This is part of an interactive course designed for absolute beginners. Humourous, real-life situations aim to make new language meaningful and maintain student interest, while students learn language functions and vocabulary. Other features of this textbook include communicative activities which offer a strong grammar base and an application cycle at the end of each unit which offers expansion exercises. Exercise instructions are given in the student book with clear examples. Each level provides 60-90 hours of instruction and a grammar survey, communicative summary and a vocabulary list appear at the end of each unit.
Keywords: English language,Ngôn ngữ tiếng Anh; Sách giáo khoa dành cho người nước ngoài